Предмет: Математика,
автор: Andrey069
B(b-1)^2-(b-5)(b^2+5b+25) упростить
Ответы
Автор ответа:
1
Пошаговое объяснение:
в(в - 1)² - (в - 5)(в² + 5в + 25) =
в(в² - 2в + 1) - в(в² + 5в + 25) + 5(в² + 5в + 25) =
в³ - 2в² + в - в³ - 5в² - 25в + 5в² + 25в + 125 =
(в³ - в³) + (-2в² - 5в² + 5в²) + (в - 25в + 25в) + 125 =
0 + (-2в²) + в - 125 = -2в² + в + 125
Похожие вопросы
Предмет: Алгебра,
автор: ulau0542
Предмет: Математика,
автор: nastyaalenus
Предмет: Физика,
автор: serezapingvin
Предмет: Физкультура и спорт,
автор: kristinapodmarkova